2020
DOI: 10.1093/cid/ciaa794
|View full text |Cite
|
Sign up to set email alerts
|

Novel Coronavirus 2019 Transmission Risk in Educational Settings

Abstract: Abstract Transmission risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in schools is unknown. Our investigations, especially in preschools, could not detect SARS-CoV-2 transmission despite screening of symptomatic and asymptomatic children. The data suggest that children are not the primary drivers of SARS-CoV-2 transmission in schools and could help inform exit strategies for lifting of lockdowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 10 publications
8
107
1
2
Order By: Relevance
“…In total, 32 studies comprising 41 640 children and adolescents and 268 945 adults were included (Table), 7,10,12, with quality and bias assessments shown in eTable 1 in the Supplement and weblinks for included studies shown in eTable 2 in the Supplement. A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 32 studies comprising 41 640 children and adolescents and 268 945 adults were included (Table), 7,10,12, with quality and bias assessments shown in eTable 1 in the Supplement and weblinks for included studies shown in eTable 2 in the Supplement. A total of 18 studies were contact-tracing studies (CTSs), 7,10,12,16-31 with 3 based in schools, [29][30][31] and 14 studies were population screening studies. 7, [32][33][34][35][36][37][38][39][40][41][42][43][44][45] Two were high quality, 33,35 22 were medium quality, 10,12,16,21,22,[24][25][26][27][29][30][31][32]34,36,38,[40][41][42][43][44][45] 7 were low quality, [17][18][19][20]…”
Section: Resultsmentioning
confidence: 99%
“…A total of 6 studies were from mainland China, 10,16,18,20,22,24 2 from the US, 25,26 and 1 each from Taiwan, 17 Japan, 19 South Korea, 12 Israel, 21 the Netherlands, 7,28 Brunei, 27 and India, 23 with 3 CTSs based in schools from Australia, 29 Ireland, 30 and Singapore. 31 Lower secondary attack rates in children and adolescents compared with adults were reported by 11 studies: 5 from provinces of China, including Hunan, 10,22 Hubei, 16,18 and Beijing, 20 and 6 from other countries, including Taiwan, 17 Japan, 19 the US, 25,26 Israel, 21 and the Netherlands, 7,28 although confidence intervals were wide in some studies. No significant differences in secondary attack rates by age were reported in 3 studies from Guangdong province, China, 24 Brunei, 27 and the states of Tamil Nadu and Andhra Pradesh in India, 23 with 1 study from South Korea 12 reporting high secondary attack rates in those younger than 19 years.…”
Section: Contact-tracing Studiesmentioning
confidence: 98%
“…Thus, detecting transmission between children specifically is difficult; quantifying it is all the more challenging. An analysis of contact tracing data from Singapore suggests that per contact transmission between children, particularly in educational settings, is low compared to adult-adult transmission [24]. Yet the number of contacts between children is expected to be significantly higher compared to other age groups [26].…”
Section: Methodsmentioning
confidence: 99%
“…During February and March, nationwide surveillance and contact-tracing in Singapore identified two SARS-CoV-2 positive students (5-year-old and 12-year-old) who attended pre-school and secondary school on the first day of their symptoms before subsequently being diagnosed with COVID-19, and one school staff who worked in a pre-school [15]. Screening of 119 students and staff who were close contacts (secondary school: n=8; pre-school 1: n=34; pre-school 2: n=77) did not detect any SARS-CoV-2 infection.…”
Section: Cohort Studiesmentioning
confidence: 99%